Genomic insights into resistome, virulome, and mobilome as organic contaminants of ESKAPE pathogens and E. coli recovered from milk, farm workers, and environmental settings in Hainan, China - Ruochen Hao; Muhammad Shoaib; Minjia Tang; Zongxi Cao; Guangliang Liu; Yan Zhang; Shengyi Wang; Ruofeng Shang; Hongjuan Zhang; Wanxia Pu (Emerging Contaminants)
The ESKAPE pathogens and E. coli are of significant public health concern and are listed among the top priorities of the World Health Organization. These pathogens are equally important for animal and public health, but their interaction with animal, human, and environmental aspects needs to be sufficiently studied. We investigated the comprehensive molecular characterization of three ESKAPE pathogens and E. coli recovered from milk, farm workers, and environmental settings in Hainan province. Minimum inhibitory concentration (MIC), extended-spectrum β-lactamase production, and biofilm production were performed per set standard protocols. The isolates were further processed by PCR and sequencing to detect resistome, virulome, and mobilome. The study found four Enterobacteriaceae species (E. coli, n=32; K. pneumoniae, n=13; E. cloacae, n=3; E. aerogenes, n=1) among n=49 bacterial isolates from the study area. Most of the strains exhibited resistance against tetracycline (71.4%), ampicillin (61.2%), florfenicol (44.9%), and ciprofloxacin (42.9%), while none of the strains was resistant against meropenem and amikacin. The MDR and ESBL-production percentages were 55.1% and 34.7 %, respectively. The resistance determinants for β-lactams (blaTEM, blaOXA-2, blaSHV, blaCTX-M), aminoglycosides (aac(3ʹ)-IIa), quinolones (qnrB, qnrS), tetracyclines (tetA, tetD), florfenicol (floR), sulfonamides (sul1, sul2), trimethoprim (dfrA14), and MDR efflux pumps (oqxA, oqxB) were detected along with diverse plasmid replicon types and integrons (intl3, 55.1%; intl1, 18.4%). The detection of virulence determinants was noted at a higher rate, and most of the strains were identified as biofilm producers by genotype (85.7%). The current study findings revealed diversified resistance and virulence determinants along with mobilome in ESKAPE pathogens and E. coli, which may pose a significant threat to human health through the food chain and environmental exposure and need immediate attention.